Missa Brevis in C 4 vocibus , 2 violinis & organo del Signor Ant.i De Lange - De Lange, Ant.
Largo: Kyrie - Allegro: Kyrie, Christe - Allegro: GLoria - Allegretto : Miserere - Alla Breve: Cum Sancto spirito - Allegro: Credo - Largo: Et Incarnatus - Allegro: Et resurrexit
complete manuscript parts: violino primo - violino 2° - Basso viola - Cornu primo - Cornu 2do - Organo - Canto - Alto - Tenore - Basso
instrumentation on frontpage does not mention the 2 horns
Keywords: Mass; Vocal music